Efficacy of a novel percutaneous pedicle screw fixation and vertebral reconstruction versus the traditional open pedicle screw fixation in the treatment of single-level thoracolumbar fracture without neurologic deficit - Rui, Lining; Li, Fudong; Chen, Cao; E, Yuan; Wang, Yuchen; Yuan, Yanhong; Li, Yunfeng; Lu, Jian; Huang, Shengchang (Frontiers in Surgery, 2023)
Abstract Objective: This study aims to compare the efficacy and safety of a novel percutaneous pedicle screw fixation and vertebral reconstruction (PPSR) and open pedicle screw fixation (OPSF) on thoracolumbar fractures. Methods: In this retrospective study, PPSR was carried in 153 patients and the other 176 patients accepted OPSF. Periprocedural characteristics, radiographic parameters, and clinical outcomes in the two groups (PPSR group and OPSF group) were assessed. Results: The operative duration (93.843±20.611 in PPSR group and 109.432±11.903 in OPSF group), blood loss (131.118±23.673 in PPSR group and 442.163±149.701 in OPSF group), incision length (7.280±1.289 in PPSR group and 14.527±2.893 in OPSF group), postoperative stay (8.732±1.864 in PPSR group and 15.102±2.117 in OPSF group), and total hospitalization costs (59027.196±8687.447 in PPSR group and 73144.432±11747.567 in OPSF group) in PPSR group were significantly lower than those in OPSF group. No significant difference was observed in complications between the two groups. The radiographic parameters including the height of the anterior vertebra, Cobb angle, and the vertebral wedge angle in the PPSR group were better improved than those in OPSF group. Recovery rates of AVH were 0.449±0.079 in the PPSR group and 0.279±0.088 in the OPSF group. And the clinical results demonstrated that, during the postoperative surgery, both the VAS score and the ODI score in PPSR group were lower than those in OPSF group. Conclusions: Compared with OPSF, PPSR has the characteristics of restoring the height of the anterior vertebra and alleviating the local kyphosis. And the VAS score and the ODI score in PPSR group were better than those in OPSF group.